2022
DOI: 10.1038/s41415-022-4978-z
|View full text |Cite
|
Sign up to set email alerts
|

'It's their mouth at the end of the day': dental professionals' reactions to oral health education outcomes

Abstract: Introduction Research has established varying levels of efficacy of oral health education (OHE) efforts. However, little is known regarding how outcomes impact dental professionals and their OHE practice. This study explores dental professionals' reactions to varying OHE outcomes and their motivations to persist with their efforts.Methods Qualitative, semi-structured interviews were conducted with dental team members working in mainly NHS general dental practices in South Wales, UK. Interviews were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Indeed, in the Humphreys et al (33) paper on Foundation Dentists experiences of delivering oral health education to adult patients, participants reported that they felt it was impossible to change patients' behaviours and there was little dental practitioners could do to influence change. This finding has been even further borne out by the findings of Barnes et al (6) who reported that dental practitioners motivation to maintain oral health education was largely dictated by the outcomes of these interactions with non-compliance by patients leading to frustration and disappointment. Foundation Dentists described parents/caregivers who were not engaging in an oral health conversation as being unmotivated.…”
Section: Motivation For Changing Behavioursmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, in the Humphreys et al (33) paper on Foundation Dentists experiences of delivering oral health education to adult patients, participants reported that they felt it was impossible to change patients' behaviours and there was little dental practitioners could do to influence change. This finding has been even further borne out by the findings of Barnes et al (6) who reported that dental practitioners motivation to maintain oral health education was largely dictated by the outcomes of these interactions with non-compliance by patients leading to frustration and disappointment. Foundation Dentists described parents/caregivers who were not engaging in an oral health conversation as being unmotivated.…”
Section: Motivation For Changing Behavioursmentioning
confidence: 95%
“…This reflects the concept of proportionate universalism in that health services need to be universal but resourced and delivered at a scale and intensity proportionate to the level of need (5). Indeed, several authors have recently argued that to improve oral health, effective oral health education and interventions are needed and that general dental practices are key in facilitating and reinforcing prevention in the community (6)(7)(8)(9)(10). As such, they advocate greater equity in dental care access, training to develop a targeted behavioural approach towards those with the greatest needs, greater engagement with users in delivery, and clear and consistent oral health messages.…”
Section: Introductionmentioning
confidence: 99%